PENERAPAN ALGORITMA LEVENSHTEIN DISTANCE DALAM APLIKASI PENGOLAHAN SURAT - Larasati, Isbalaikana; Marisa, Fitri (DINAMIKA DOTCOM, 2019)
The application of a letter processing system is expected to provide an advantage for a company. In designing a letter processing application, you can use the Levenshtein Distance method, where two strings of Levenshtein distance are the minimum number of operations needed to convert a string to another string. Levenshtein distance is also used to measure the value of similarity or similarity between two words (strings). So that it can simplify the process of finding mail archives. An example of the word used is sirat as the source word and letter as the target word, selling as the source word and submission as the target word, trading as the source and travel word as the target word. The results of the comparison of the word sirat and letters get the results of the distance comparison 1. While the word sales and submission has a distance comparison result 4. And in the word trade and travel has a distance comparison result 3. Keywords: Information Systems, Letter Archiving, Levenshtein Distance Algorithms